Direct visualization of the interaction between pilin and exopolysaccharides of Myxococcus xanthus with eGFP fused PilA protein - Hu, Wei (2011)
Type IV pili (TFP) and exopolysaccharides (EPS) are important components for social behaviors in Myxococcus xanthus, including gliding motility and fruiting body formation. Although specific interactions between TFP and EPS have been proposed, direct observations of these interactions under native condition have not yet been made. In this study, we found that a truncated PilA protein (PilACt) which only contains the C-terminal domain (amino acids 32-208) is sufficient for EPS binding in vitro. Furthermore, an enhanced green fluorescent protein (eGFP) and PilACt fusion protein was constructed and used to label the native EPS in M. xanthus. Under confocal laser scanning microscope, the eGFP-PilACt-bound fruiting bodies, trail structures and biofilms exhibited similar patterns as the wheat germ agglutinin lectin (WGA)-labeled EPS structures. This study showed that eGFP-PilACt fusion protein was able to efficiently label the EPS of M. xanthus and for the first time provided evidence for the direct interaction between the PilA protein and EPS under native conditions.